The The Effect of Blood Transfusion Frequency on Secretor Status Titer in Saliva and Urine Specimens of Thalassemia Patients - Darmantoputro, Feby Wicaksono; Nurhayati, Betty; Hayati, Eem; Marliana, Nina (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Thalassemia is a disease caused by a deficiency or loss of synthesis of one or more normal globin chains. In diseases that require blood transfusions, such as Transfusion Dependent Thalassemia (TDT), it is very important to examine the blood type to determine the blood to be transfused. The ABO blood type system antigen or secretor, is found in body fluids in the form of dissolved antigens, including in saliva and urine. Interference can be caused by the frequency of transfusion, which can change the secretor content in the saliva and urine of thalassemia patients, causing false negatives in the examination of secretor status. Objectives: This study aims to determine the effect of transfusion frequency on the titer of secretor status in saliva and urine specimens of Thalassemia patients. Materials and Methods: The type of study is quasi-experimental, Agglutination-Inhibition method. The research sample was 23 Thalassemia major patients. 15 patients are secretor patients, with a frequency of 1x transfusion a month were 7 people (47%), a frequency of 2x transfusion a month were 5 people (33%), and 4x transfusion a month were 3 people (20%). Results: The results of the study on Thalassemia patients obtained from saliva were titers between 1/8 to 1/256. From urine, the results were non-secretors. In contrast to previous studies, which stated that urinary is still detected but four times weaker than saliva. Based on the ANOVA statistical calculation, sig. 0.909 (p>0.05) was obtained. Conclusions: The conclusion is that there is no effect of transfusion frequency on the titer of secretor status in saliva or urine.